Haemodyanamic Evaluation Of Intraspinal Xylazine And Ketamine Combinations In Buffalo Calves - Pathak, Rekha; Pratap, Krishna; Pal , Amar (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Present study evaluates the xylazine-ketamine combination analgesia at the lumbosacral space, based on hemodynamic parameters in 12 buffalo calves. Clinically healthy, male buffalo calves ranging 6-8 months of age weighing 55-75 kgs were used. Ketamine 2.5 mg/kg + xylazine 0.05mg/ kg was given intraspinally at lumbosacral space. Onset, duration of analgesia was measured and hemodynamics studies were carriedout by measuring MAP, CVP and ECG values before and after injection. The onset of analgesia took 2.6±0.4 min. Ketamine-xylazine produced a moderate analgesia of thorax, abdomen and flank and complete analgesia of digits, perineum, inguinal region, hind limbs and tail. Total duration of analgesia was 20 minutes. MAP reduced and CVP was not much affected, bradycardia and arrhythmia was noticed. Depressed ECG parameters were seen. It provides good spinal analgesia. Although it has a significantly depressing effect in the said dose over the heart functions. The changes were reversible with time and hence it can be used as a safe spinal analgesic but should be used with caution in cardiac patient.
Keywords: Xylazine-Ketamine Combination; Spinal; Buffalo Calves; Analgesia